Electron transfer coupling with biogenic elements conversion in farmland soil: A review - Sihan Zhao; Guang Yang; Yuewei Yang; Xin Yu; Jialu Sun; Xiaolin Zhang; Pinpin Yang; Xiaodong Zhao; Xiaojing Li (Soil and Tillage Research, 2026)

Electron Transfer Drives Preferentially Assimilatory Sulfate Reduction in Petroleum‐Contaminated Soil - Jialu Sun; Yuewei Yang; Xin Yu; Xiaolin Zhang; Pinpin Yang; Bingyang Liu; Yali Chen; Dejun Wang; Xinhong Peng; Xiaojing Li (Environmental Microbiology, 2026)
Sulfur is a vital macroelement for soil fertility and crop growth, and its bioavailability is converted with electron flux. To determine the effect of biological electron transfer on the sulfur cycle in soil, a microbial electrochemical system (MES) was established to amplify the efficiency of extracellular electron transfer. Results showed that biocurrent obviously promoted the reduction of water‐soluble SO 4 2‐ to S 2− , and afterward reoxidised to fulvic acid sulfur (FAS, 32% increment) instead of humic acid sulfur (HAS, 77% decrement). The δ 34 FAS values (12‰ to 24‰) were consistent with the typical isotopic signatures of dissimilatory sulfate reduction, while the δ 34 HAS values (−40‰ to −60‰) matched the assimilatory sulfate reduction. Meanwhile, the assimilatory SO 4 2‐ reduction to cysteine improved with a 30%–33% increase for the NAD + /NADH and secretion of cytochrome c to support robust redox. Essentially, the precursor‐product pairs of desulfonation were enhanced by 26%–93%. Compared to a 6% contribution of HAS, the formation of cysteine accounted for 55% of the electron transport flux. According to screening 32 sulfur‐transforming genes, 609 genera were identified, especially 31%–84% proliferation for Desulfatitalea . This study reveals ways of organic sulfur conversion mediated by electron transfer, which can assist the biological amendment of sulfur bioavailability in soil.

Full-Process simulation and risk assessment framework for compound flooding in inland cities with high external inflow - Chenchen Fan; Jingming Hou; Donglai Li; Yongping Yang; Gangfu Song; Tian Wang; Jiahao Lv; Xuan Li; Guangzhao Chen; Peiqi Zhang; Yanhong Wang; Bingxue Li; et al. (Journal of Hydrology, 2026)

Identification, antioxidant and acetylcholinesterase inhibitory activities of soluble and insoluble-bioactive components from Cinnamomum camphora seed kernel residue - Pinpin Zhang; Junmin Long; Zheling Zeng; Xianghui Yan; Yujing Yang; Rongping Fu; Yuling Lin; Deming Gong; Cheng Zeng; Ping Yu (Food Research International, 2026)

Advances in fabrication, properties, and applications of homo- and heterostructural moiré engineering - Weihua Yang; Ruijie Chen; Pinpin Cao; Yang Bai; Wenhui Guo; Zhiyuan Gu; Xiaopeng Fan (Chemical Engineering Journal, 2026)

Soil photocatalysis revisited: Unveiling potential in organic contaminant remediation - Pengju Zhong; Xiaolin Zhang; Xin Yu; Side Yang; Pinpin Yang; Tian Li; Xiaodong Zhao; Xiaojing Li (Chemical Engineering Journal, 2025)

Community-level polycyclic aromatic hydrocarbon exposure and circulating microRNAs: Exploring their origins and regulatory functions in immune cells - Yufei Wang; Wending Li; Xuedan Xu; Yaxin Wang; Qin Jiang; Yutong You; Ruochen Yuan; Xiao Zhang; Yang Xiao; Chan Kong; Tingting Mo; Huan Guo; et al. (Journal of Hazardous Materials, 2025)

Ferrihydrite redox enhanced biodegradation of petroleum hydrocarbons coupling with conversion of soil multi-elements by electron transfer - Xin Yu; Xiaolin Zhang; Pinpin Yang; Jialu Sun; Yuewei Yang; Xiaodong Zhao; Guang Yang; Penghui Li; Xiaojing Li (Journal of Hazardous Materials, 2025)

Efficient urban flood control and drainage management framework based on digital twin technology and optimization scheduling algorithm - Chenchen Fan; Jingming Hou; Xuan Li; Gangfu Song; Yihui Yang; Xin Liang; Qingshi Zhou; Muhammad Imran; Guangzhao Chen; Ziyi Wang; Pinpin Lu (Water Research, 2025)

Enhancing tetracycline removal: Performance and mechanisms of interspecies electron transfer in microbial consortia - Zhennan Wang; Huike Ye; Xiaojing Li; Yang Sun; Lixia Zhao; Yali Chen; PinPin Yang; Liping Weng; Mohan Bai (Journal of Hazardous Materials, 2025)

Controllable fabrication of hierarchical porous anode for exoelectrogens internal colonization in microbial electrochemical system - Yujie Zhu; Dandan Liang; Ruize Gu; Shujuan Liu; Pinpin Yang; Lijuan Zhang; Weihua He; Yujie Feng (Bioresource Technology, 2025)

Fe-N doping boosts the performance of extracellular electron transfer from lignocellulose reconstruction-based microbe-electrode in microbial electrochemical systems - Pinpin Yang; Changwen Shi; Xiaojing Li; Xiaolin Zhang; Huike Ye; Yujie Zhu; Weihua He; Yujie Feng (Chemical Engineering Journal, 2025)

Tetracycline removal by immobilized indigenous bacterial consortium using biochar and biomass: Removal performance and mechanisms - Xinping Yu; Mohan Bai; Xiaojing Li; Pinpin Yang; Qiuzhen Wang; Zhennan Wang; Liping Weng; Huike Ye (Bioresource Technology, 2024)

Evaluating the embryotoxicity of benzophenone-based photoinitiators in stem cells and zebrafish embryos - Chen-Yi Weng; Tzu-Ching Chang; Jun-Yang Liou; Ju-Hsin Hsu; Chia-Chi Ho; Salim Arrokhman; Pinpin Lin (Toxicology, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

Effect of lignocellulosic biomass components on the extracellular electron transfer of biochar-based microbe-electrode in microbial electrochemical systems - Pinpin Yang; Yu Han; Lefei Xue; Yaqian Gao; Jia Liu; Weihua He; Yujie Feng (Journal of Water Process Engineering, 2024)

Associations of multiple plasma metals with osteoporosis: findings from the Dongfeng-Tongji cohort - Xuedan Xu; Junrui Lyu; Pinpin Long; Kang Liu; Hao Wang; Xi Wang; Yu Yin; Handong Yang; Xiaomin Zhang; Huan Guo; Meian He; Tangchun Wu; et al. (Environmental Science and Pollution Research, 2023)

The restricted mass transfer inside the anode pore channel affects the electroactive biofilms formation, community composition and the power production in microbial electrochemical systems - Pinpin Yang; Yaqian Gao; Naiyu Wang; Yujie Zhu; Lefei Xue; Yu Han; Jia Liu; Weihua He; Yujie Feng (Science of The Total Environment, 2023)

Liquid-gas phase transition enables microbial electrolysis and H2-based membrane biofilm hybrid system to degrade organic pollution and achieve effective hydrogenotrophic denitrification of groundwater - Yu Han; Pinpin Yang; Yujie Feng; Naiyu Wang; Xiaole Yuan; Jingkun An; Jia Liu; Nan Li; Weihua He (Chemosphere, 2023)

Liquid-gas phase transition enables microbial electrolysis cell to treat organic pollution and synchronously remediate nitrate-contaminated groundwater via hydrogenotrophic denitrification - Yu Han; Yujie Feng; Naiyu Wang; Pinpin Yang; Guofang Ding; Jingkun An; Jia Liu; Nan Li; Weihua He (Journal of Cleaner Production, 2023)

Lignocellulose reconstituted shape-controllable self-supporting carbonaceous capacitance-anodes with high electron transfer rates for high-performance microbial electrochemical system - Pinpin Yang; Yaqian Gao; Lefei Xue; Yu Han; Jingkun An; Weihua He; Yujie Feng (Bioresource Technology, 2023)

A three-dimensional phenolic-based carbon anode for microbial electrochemical system with customized macroscopic pore structure to promote interior bacteria colonization - Yaqian Gao; Jianjun Huang; Lijuan Zhang; Yujie Zhu; Pinpin Yang; Lefei Xue; Naiyu Wang; Weihua He (Science of The Total Environment, 2023)

Anaerobic ammonium oxidation and denitrification in a paddy soil as affected by temperature, pH, organic carbon, and substrates - Jun Shan; Pinpin Yang; Xiaoxia Shang; M. Mizanur Rahman; Xiaoyuan Yan (Biology and Fertility of Soils, 2018)